Predicting the Effects of Climate Change on the Suitable Habitat of Japanese Spanish Mackerel (Scomberomorus niphonius) Based on the Species Distribution Model - Yang, Tianyan; Liu, Xingyu; Han, Zhiqiang (Frontiers in Marine Science, 2022)
Japanese Spanish mackerel (Scomberomorus niphonius) is an important commercial fish species with a seasonal migratory habit in China. At present, no study has reported the seasonal variation of its potential suitable habitat. Therefore, we used biomod2 ensemble model to predict the potential suitable habitat of S. niphonius in different seasons through its current distribution sites and future environmental variables. Our results showed that the ensemble model had a high accuracy, with true skill statistics and receiver operator characteristic values of 0.91 and 0.98, respectively. Under the Representative Concentration Pathway (RCP) 4.5 scenario, the reduction rate of suitable habitats in summer of 2050 will be 33.2%, and those for the rest of the seasons will reach 3.5%. The reduction rate in summer of 2100 will be 43.5%, and those for the remaining seasons will reach 6.5%. In addition, this reduction rate will become more serious with the increase in emission scenario and time, especially in the RCP8.5 in which the summer reduction rate is as high as 88.9%. Habitat changes in summer show a strong temperature sensitivity. The distribution centroid of S. niphonius will shift to higher latitudes under RCP 4.5 and RCP 8.5. Depth and temperature are the two most important factors that affect the distribution of this species. The results can provide basic data for understanding the adaptability of S. niphonius to climate change and establishing an elastic ecosystem.